Feminist Semiotics of “Safe”: Intimate Violence in the Time of Pandemic - Preser, Ruth (Violence against women, 2023)
This article explores the discursive politics of intimate partner violence during the first COVID-19 lockdown in Israel. It asks how, despite greater awareness and recognition, intimate violence disappeared from the mindset of those managing the pandemic, even as it soars. The analysis traces the conditions that enable the dialectic of presence–disappearance, by reading the ideological prescriptions in policy papers, parliamentary debates, court appeals, and media debates. I argue that disregard of intimate violence is made possible by the idealization of home and family as spaces of security and protection, coupled with the mobilization of militaristic measures and discourses.